On the martingale representation theorem and approximate hedging a contingent claim in the minimum mean square deviation criterion - Huu, Nguyen Van; Hoang, Vuong Quan (VNU Journal of Science: Mathematics - Physics, 2007)
Abstract. In this work vve consider the problem of the approximate hedging of a contingent claim in minimum mean square deviation criterion. A theorem on martingaỉe representation in the case of discrete time and an application of obtained result for semi-continous market model are given. Keywords: Hedging, contingent claim, risk neutral martingale measure, martingale represen- tation.